Pharmacological modulation of aversive responsiveness in honey bees - Tedjakumala, Stevanus R.; Aimable, Margaux; Giurfa, Martin (Frontiers in Behavioral Neuroscience, 2014)
Within a honey bee colony, individuals performing different tasks exhibit different sensitivities to noxious stimuli. Noxious-stimulus sensitivity can be quantified in harnessed bees by measuring the sting extension response (SER) to a series of increasing voltages. Biogenic amines play a crucial role in the control of insect responsiveness. Whether or not these neurotransmitters affect the central control of aversive responsiveness, and more specifically of electric-shock responsiveness, remains unknown. Here we studied the involvement of the biogenic amines octopamine, dopamine and serotonin, and of the ecdysteroid 20-hydroxyecdisone in the central control of sting responsiveness to electric shocks. We injected pharmacological antagonists of these signaling pathways into the brain of harnessed bees and determined the effect of blocking these different forms of neurotransmission on shock responsiveness. We found that both octopamine and 20-hydroxyecdisone are dispensable for shock responsiveness while dopamine and serotonin act as down-regulators of sting responsiveness. As a consequence, antagonists of these two biogenic amines induce an increase in shock responsiveness to shocks of intermediate voltage; serotonin, can also increase non-specific responsiveness. We suggest that different classes of dopaminergic neurons exist in the bee brain and we define at least two categories: an instructive class mediating aversive labeling of conditioned stimuli in associative learning, and a global gain-control class which down-regulates responsiveness upon perception of noxious stimuli. Serotonergic signaling together with down-regulating dopaminergic signaling may play an essential role in attentional processes by suppressing responses to irrelevant, non-predictive stimuli, thereby allowing efficient behavioral performances.